2011
DOI: 10.1111/j.1365-2729.2011.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I'm a completely different person at home’: using digital technologies to connect learning between home and school

Abstract: This paper reports on a qualitative study exploring children's, parents', and teachers' experiences of communication between home and school and connections between children's learning at school and home in order to consider how using digital technologies to mediate the home-school relationship might support children's learning. Parents, teachers, and children welcomed the idea of using digital technologies to communicate between home and school, hoping that more timely communication could avoid problems at sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 19 publications
0
27
0
3
Order By: Relevance
“…The evidence for this was that only one school mentioned the importance of home-school cooperation and parental involvement in their vision description, and only a few schools provided information about the parental board. This could give rise to parents' negative perceptions and feelings about the fact that the school does not expect and trust the value of parental involvement, and could prevent their real involvement and influence (Grant, 2011;Hornby & Lafaele, 2011). The results also indicate that schools' expectations for parental involvement in education are more likely to be limited to the social aspects of student development (such as detailed information about the lunch menu, students' healthcare, and local policies and regulations for working toward equal treatment and against discrimination) rather than the pedagogical issues (absence of lesson schedule, class activities, students' choices, and students' work and progression).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for this was that only one school mentioned the importance of home-school cooperation and parental involvement in their vision description, and only a few schools provided information about the parental board. This could give rise to parents' negative perceptions and feelings about the fact that the school does not expect and trust the value of parental involvement, and could prevent their real involvement and influence (Grant, 2011;Hornby & Lafaele, 2011). The results also indicate that schools' expectations for parental involvement in education are more likely to be limited to the social aspects of student development (such as detailed information about the lunch menu, students' healthcare, and local policies and regulations for working toward equal treatment and against discrimination) rather than the pedagogical issues (absence of lesson schedule, class activities, students' choices, and students' work and progression).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that schools' frequent communication and interaction with parents are the strongest premise for school practices of parental involvement to support children's learning at home and at school (Grant, 2011). Research has also indicated that home-school communication is a primary way to enhance trust in the home-school relationship, and that trust is a vital component of effective collaboration between home and school.…”
Section: Information and Communication -Preconditions For Parental Inmentioning
confidence: 99%
“…Frequent communication with parents helps reinforce and strengthen student learning at home, fosters greater parental interest and engagement in school activities, fuels more positive student attitudes about school and learning, and raises parents' educational expectations and aspirations for their children (Joshi, Eberly, & Konzal, 2005). Though often overlooked, or neglected by school personnel, open, clear, welcoming and effective communication can serve as the relational glue that helps bind parents, teachers, principals and support staff together in pursuit of shared goals and high expectations for all children (Grant, 2011;Joshi et al, 2005;Thompson & Raikes, 2007). When nurtured and sustained over time, communication builds trust between school personnel and parents, and fosters a climate of mutual respect and reciprocity that helps both parties work through any concerns, disagreements, or conflicts in a productive and beneficial manner (Thompson et al, 2007).…”
Section: School-home Communicationmentioning
confidence: 99%
“…Estudios como los de Sánchez et al (2010) en Chile y el de Grant (2011) en Inglaterra demuestran que los jóvenes creen que es importante el uso de NT en sus vidas, pero perciben brechas importantes entre el contexto escolar y cotidiano. Selwyn, Potter y Cranmer (2009) muestran en un estudio etnográfico a alumnos de primaria que cuando se habla de conexión entre aprendizaje en el colegio y hogar, los entrevistados se centran en las tareas escolares; poco se trae del colegio a la casa y la experiencia escolar es muy diferente a lo que ocurre en sus hogares.…”
Section: Necesidad De Mayor Investigación Empírica Sobre Las Tnaunclassified